Echinacea purpurea (L.) Moench crude extract combined with citric acid inactivates Cronobacter sakazakii isolated from powdered infant formula - Peng Fei; Yaping Yu; Chen Liang; Ruxue Fang; Yujun Jiang; Ling Guo (Journal of Dairy Science)
ABSTRACT: The objective of this study was to reveal the synergistic antibacterial activity and mechanism of Echinacea purpurea (L.) Moench crude extract (EE) and citric acid (CA) against Cronobacter sakazakii isolated from powdered infant formula (PIF). The minimum inhibitory concentration (MIC) of EE against C. sakazakii was determined, and then growth curve and time-kill analysis were used to screen the optimal antibacterial combination of 1 MIC of EE and CA. Changes in cell membrane potential, cell integrity, cell permeability, bacterial protein, DNA, and intracellular reactive oxygen species (ROS) levels, and cell morphology of C. sakazakii were used to reveal the synergistic inhibitory mechanism of EE and CA. The inactivation effect of EE in combination with CA against C. sakazakii on common contact surfaces was used to evaluate its efficacy as a natural disinfectant. The results showed that the MIC value of EE against C. sakazakii was 60 mg/mL, and the growth curve of C. sakazakii treated by 1 MIC of EE combined with CA (pH 3.0) was significantly inhibited compared with the control groups. The results of time-kill analysis showed that after combined treatment with 1 MIC of EE and CA (pH 3.0) for 30 min, approximately 8 log cfu/mL of C. sakazakii were inactivated. Cell membrane hyperpolarization, damaged cell membrane integrity, improved cell membrane permeability, decreased bacterial protein and DNA levels, increased and then decreased intracellular ROS contents, and deformed and ruptured cell morphology were found in C. sakazakii treated by EE combined with CA, and these phenomena were more pronounced than in C. sakazakii treated by EE or CA alone. When inoculated stainless steel, glass, ceramic, polystyrene, bamboo, and wood were sprayed with 1 MIC of EE combined with CA (pH 3.0) and after 15 min of treatment, approximately 5 log cfu/mL of C. sakazakii were inactivated. These findings suggest that EE combined with CA can effectively inactivate C. sakazakii isolated from PIF and can be used as a natural disinfectant to reduce the contamination of C. sakazakii in PIF production environments or households.